Reconstructing diet and pottery technology of the Early Bronze Age 'Kura-Araxes culture': a multi-analytical approach - Manoukian, N (2021)
The Kura-Araxes (KA) cultural phenomenon, dated to the Early Bronze Age (EBA, 4th and 3rd millennium, c. 3500-2500 BCE) is primarily characterised by the emergence of a homogeneous ‘material culture package’ in settlements across the South Caucasus (Georgia, Armenia, and Azerbaijan), as well as territories extending to the Levant and Ancient Near East. More specifically, one of the major EBA craft products associated with the KA corresponds to a homogeneous style of black-burnished pottery in the South Caucasus, known as Early Transcaucasian Ware and other synonymous terms in the literature.